Collaborative Governance for Reopening Schools in Indonesia Following the COVID-19 Pandemic - Hendarman, Hendarman (KnE Social Sciences, 2022)
Due to COVID-19, there has been a change in the teaching process and climate in schools and universities. Teaching that was originally carried out face-to-face was changed to online learning. This study was carried out to examine how a policy to accelerate the opening of face-to-face learning known as Surat Keputusan Bersama 4 Menteri or a Joint Decree of 4 Ministers (namely the Minister of Religion Affairs, of Health, of Home Affairs, and of Education, Culture, Research and Technology) has been implemented and its impact. This joint decree regulates how schools are allowed to open after a reduction in cases of COVID-19. Data were collected from relevant regulations, government documents and scientific papers. It was revealed that this joint decree, which is based on the roles and responsibilities of each ministry at the central and region level, has been differently perceived and implemented. The success of accelerating school openings is determined by the level of collaborative governance where the related elements, namely local government, schools, parents and the community, understand their respective roles and are open and accountable to any existing problems and mitigation actions when new clusters emerge. The leadership of regional heads is the key to the safety and health of students and education personnel in conducting face-to-face learning after COVID-19. In addition, media campaigns must be encouraged to achieve a common perception among various stakeholders. Keywords: school reopening, post-COVID-19, Indonesia, collaborative governance